A SEMIOTIC ANALYSIS FOUND ON A POSTER IN KITKAT INSTAGRAM ACCOUNT - Pratama, I Gde Saputra; Suastini, Ni Wayan (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This study discusses the importance of effective communication in exchanging information and ideas between individuals through verbal and visual signs. A semiotic approach is used to analyze the meaning contained in the Instagram KitKat poster. The theory of Saussure (2011) and Barthes (1977) was used to analyze the verbal and visual signs on the posters. The aim of this analysis is to understand what verbal and visual signs are and to uncover the complex messages behind their surface appearances, highlighting how signs are used to convey each meaning. Three KitKat posters from the @kitkat account were reviewed, revealing a dynamic brand communication strategy. This analysis shows how verbal signs such as slogans and brand names relate to visual signs such as images and symbols to create subtle narratives about KitKat posters that imply the meaning of always enjoying KitKat during break time. This research increases the understanding of how brands use semiotics to build strong messages across various dimensions ofÂ communication.